Mercury levels in fish of Trombetas River, lower Amazon: an area out of gold mining influence - Faial, Kleber Raimundo Freitas (2016)
The bioaccumulation of Hg in fish of different feeding habits was evaluated in the Trombetas River, tributary of the Amazon River, in an area without records of gold mining. The objectives of the present study was to generate information on Hg concentrations in the main fish species consumed in this area, provide a database with information from other Amazonian basins, and to establish normal values for the region. The fish samples were obtained and identified with popular and scientific names with the aid of local fishermen. The Hg analyses were carried out by atomic absorption spectrometry with generation system of Hg cold vapor after acid digestion. The species were divided in five groups and the Hg concentrations varied widely with the position occupied in the trophic chain and the food habito Higher values were found in the carnivorous and piscivorous fish with Hg mean concentrations of 0.218 ug/g (muge 0.047-0.875 ug/g) and 0.357 ug/g (range 0.036-1.336 ug/g), respectively. To elucidate the origin ofHg in this fish species and the possibility of exposure of resident populations in this area is necessary to consider, among other factors, the migratory characteristics of different fish species and aspects of the aquatic ecosystem, including bottom sediments, suspense particles, water, and geological substratum. In this study, it was found Hg levels in fish above the expected, indicating that an extensive search for the origins ofthis metal should be carried in Amazon ecosystems. These studies should clarify to Amazon populations if they are or not exposed to Hg. Moreover, it is necessary to include the monitoring of Hg concentrations in fish consumed by the Amazon populations in surveillance health programs and to implement programs of environmental education comprising the selective consumption of fish.